Three-dimensional geometric morphometric shape analysis of chest wall kinematics in different breathing conditions - Marta Gómez-Recio; Markus Bastir; Antonella LoMauro; Andrea Aliverti; Benoit Beyer (Royal Society Open Science, 2024)
Breathing motion is based on the differential activity of the thoracic, diaphragmatic and abdominal muscles. Muscle contributions differ between rest and exercise conditions and depend on posture and other factors. Traditionally, these changes are investigated on volumetric data using optoelectronic plethysmography (OEP). OEP offers insight into size variations of different chest wall (CW) compartments but does not provide three-dimensional visualization methods of CW breathing kinematics. Here we explore the use of three-dimensional geometric morphometrics to analyse size and shape changes caused by spontaneous breathing motion during quiet (QB), and recovery breathing (REC, immediately after heavy exercise) in two different postures (SIT, sitting on cycle ergometer; STA, standing position). Our findings show that size and shape differ significantly between inspiration and expiration and that differences are greater in REC than in QB. However, this is achieved by stronger expiration in SIT but by greater expiratory and inspiratory movements in STA. Shape analysis suggests that these differences may be attributed to constrained mobility of the shoulder girdle and a minor thoracic spine extension during inspiration owing to position on the ergometer. Breathing motion in STA seems biomechanically less constrained. Geometric morphometrics analyses can provide additional insights into data obtained by OEP.